A propensity-matched study of the association between pre-pregnancy maternal underweight and perinatal outcomes of singletons conceived through assisted reproductive technology. Issue 4 (October 2019) - Qu, Pengfei; Liu, Fangfang; Zhao, Doudou; Wang, Yongbo; Wang, Min; Wang, Linyu; Dang, Shaonong; Wang, Duolao; Shi, Juanzi; Shi, Wenhao
Abstract: Research question: Is pre-pregnancy maternal underweight associated with perinatal outcomes of singletons who were conceived through assisted reproductive technology (ART)? Design: A 10-year (2006–2015) Chinese sample of 6538 women and their singleton infants who were conceived through ART was used to examine the association between pre-pregnancy maternal underweight and perinatal outcomes. Propensity scores for underweight were calculated for each participant using multivariable logistic regression, which was used to match 740 (91.36% of 810) underweight women with 740 normal weight women; the effects of underweight on birth weight and gestational age were then assessed by generalized estimating equation model. Results: After propensity score matching, the birth weight was lower (difference –136.83 g, 95% CI –184.11 to –89.55 g) in the underweight group than in the normal weight group. The risks of low birth weight (LBW) and small for gestational age (SGA) were increased in the underweight group compared with those in the normal weight group (LBW: RR 1.64, 95% CI 1.01 to 2.67; SGA: RR 1.46, 95% CI 1.06 to 2.02). The risks of fetal macrosomia and being large for gestational age (LGA) were decreased in the underweight group compared with those in the normal weight group (macrosomia: RR 0.39, 95% CI 0.26 to 0.61; LGA: RR 0.36, 95% CI 0.24 to 0.53). The associations between underweight, gestational age and preterm birth were not statistically significant. Conclusions: Among women undergoing ART, pre-pregnancy maternal underweight was associated with lower birth weight, increased LBW and SGA risks, and decreased fetal macrosomia and LGA risks in singleton infants.